Does fluoride exposure impact on the human microbiome? - Moran, Gary; Zgaga, Lina; Daly, Blanaid (My University, 2023)
Fluoride is added to drinking water in some countries to prevent tooth decay (caries). There is no conclusive evidence that community water fluoridation (CWF) at WHO recommended concentrations for caries prevention has any harmful effects. However, research is ongoing regarding potential effects of ingested fluoride on human neurodevelopment and endocrine dysfunction. Simultaneously, research has emerged highlighting the significance of the human microbiome in gastrointestinal and immune health. In this review we evaluate the literature examining the effect of fluoride exposure on the human microbiome. Unfortunately, none of the studies retrieved examined the effects of ingested fluoridated water on the human microbiome. Animal studies generally examined acute fluoride toxicity following ingestion of fluoridated food and water and conclude that fluoride exposure can detrimentally perturb the normal microbiome. These data are difficult to extrapolate to physiologically relevant human exposure dose ranges and the significance to humans living in areas with CWF requires further investigation. Conversely, evidence suggests that the use of fluoride containing oral hygiene products may have beneficial effects on the oral microbiome regarding caries prevention. Overall, while fluoride exposure does appear to impact the human and animal microbiome, the long-term consequences of this requires further study.
PUBLISHED
Keywords: Bacteria; Caries; Community water fluoridation; Fluoride; Fluorosis; Microbiome; Immunology, Inflammation & Infection; Epidemiology; Health outcomes; Medicine; Public health; Chronic Health Condition; Health